A multidisciplinary diabetic foot protocol at chiang mai university hospital: Cost and quality of life - Rerkasem K. (2014)
The consensus is that a multidisciplinary approach for patients with diabetic foot ulcer is effective in reducing the number of leg amputations. Concern remains, however, about cost and health-related quality of life issues. From August 2005 to March 2007, a multidisciplinary diabetic foot protocol (DFP) was used at the authors?